Declining incidence of episodes of asthma: a study of trends in new episodes presenting to general practitioners in the period 1989–98. Issue 8 (1st August 2000) - Fleming, D M; Sunderland, R; Cross, K W; Ross, A M
Abstract : BACKGROUND: A study was undertaken to determine trends in the incidence of new episodes of asthma presented to general practitioners participating in the Weekly Returns Service of the Royal College of General Practitioners, comprising 92 practices with a registered population of approximately 680 000 persons well distributed throughout England and Wales. These practices monitor the morbidity presented at every consultation, distinguishing between new episodes of illness and ongoing consultations. METHODS: Age specific weekly rates of new episodes of asthma (and of acute bronchitis) presenting to the general practitioners over the years 1989–98 were examined in four week blocks and analysed by multiple regression, separating secular from seasonal trends. RESULTS: Quadratic trends in episodes of asthma were evident in each of the age groups with peaks in 1993/4. Corresponding analyses for acute bronchitis disclosed similar trends generally peaking in the winter of 1993/4. Mean weekly incidence data (all ages combined) decreased in all quarters since 1993. Regional analysis (North/Central/South) showed similar decreases. CONCLUSIONS: There has been a gradual decrease in the incidence of asthma episodes and of acute bronchitis presenting to general practitioners since 1993. The trend of an increase before 1993 followed by a decrease cannot be explained by changes in the patterns of health care usage or diagnostic preference of doctors.